Environmental variables and their relationship to life quality inNasiriyah City - Taih, Ali Dhaaeif (Thi Qar Arts Journal, 2024)
The study aims to assess air quality, the quality of clear and potable water, and the nature of solid household waste and their impact on the quality of life in the study area. The study area was divided into four sectors to facilitate comparison. To determine air quality, the researcher took four samples from the study area sectors, with one sample per sector, to calculate air pollutant concentrations (CO, SO2, O3, NO2, PM10) in the study area. The linear interpolation equation (AQI) was applied to show air quality. Similarly, to measure the quality of clear and potable water, one sample was taken from each sector to calculate water pollutant concentrations (T.D.S, Tub, pH, T.H, Cl, Ca, Mg, Na, SO4, TPC) using the Weighted Arithmetic Water Quality Index (WAMI) to indicate the quality of clear and potable water in the study area. The study also addressed the spread of solid household waste and identified daily and monthly quantities. Furthermore, the researcher surveyed the opinions of the area’s residents through 400 questionnaire forms, with 100 forms distributed per sector, to understand their views on environmental variables. The study found that environmental variables indicate continuous deterioration due to various factors, including population growth and the lack of proper planning to address these issues, negatively impacting the quality of life in the study area. As a result, residents expressed dissatisfaction with their surrounding environment and their unwillingness to live in such conditions, as shown by the analysis of both objective and subjective indicators of quality of life in Nasiriyah city.